The Political Economy of Southeast Asia
XXVI, 412 p. 13 illus.
Keywords: “No course on Southeast Asia can afford to miss this book as its core text.” Professor Amitav Acharya, American University, USA “A book that every student of Southeast Asia needs to read.” Professor Edward Aspinall, Australian National University, Australia “This book does what a work on political economy should do… pathbreaking”. Walden Bello, State University of New York at Binghamton, USA “Ambitious… impressive… a model of engaged scholarship with global resonance. Bravo!” Professor Tania Li, University of Toronto, Canada “The most compelling theoretical and empirical political economy book available on Southeast Asia.” Professor Adam David Morton, University of Sydney, Australia “A vital book for all scholars, students and practitioners concerned with political economy and development”. Professor Nicola Philips, Kings College London, UK “Will not only be of immense interest to scholars studying Southeast Asia, but also those seeking to understand the multifaceted nature of the political economy of uneven development in contemporary capitalism.” Professor Susanne Soederberg, Queen’s University, Canada This all-new fourth edition of The Political Economy of Southeast Asia constitutes a state-of-the-art, comprehensive analysis of the political, economic, social and ecological development of one of the world’s most dynamic regions. With contributions from world-leading experts, the volume is unified by a single theoretical approach: the Murdoch School of political economy, which foregrounds struggles over power and resources and the evolving global context of hyperglobalisation. Themes considered include gender, democracy, populism, state transformation, regional governance, migration, aid, extractive industries, and the environment. The volume will be useful for scholars and students across multiple disciplines, including political economy, development, international relations and area studies, and for civil society, policymakers, and anyone with a stake in the future of this fascinating region. Toby Carroll is Associate Professor in the Department of Asian and International Studies, City University of Hong Kong. Shahar Hameiri is Associate Professor in the School of Political Science and International Studies, University of Queensland. Lee Jones is Reader in the School of Politics and International Relations, Queen Mary University of London.